Islam in education: how marginalizing Islamic curriculum from Egypt's national education has contributed to religious extremism - Shaker, Thanaa (ATTARBIYAH: Journal of Islamic Culture and Education, 2023)
This study investigates the impact of marginalizing religious curriculum in the public-school system on the tolerance levels among Egyptian youth. Unlike previous research associating religious instruction with radicalization, this study offers new perspectives on the detrimental effects of marginalizing religious education in fostering tolerance. It argues that a balanced religious education can prevent the radicalization of young individuals by extremist groups. The central question is whether education significantly influences the radicalization process. The argument suggests that the secularization of education has intensified interest in Islam, leading to polarization fueled by radical factions with pre-existing objectives. Using a qualitative methodology, specifically a case study design, the research conducted interviews with 57 participants from the national school background. Findings reveal that marginalizing Islamic curricula has adverse effects on promoting tolerance among youth. The study aims to provide education officials with insights into the negative consequences of marginalizing religious curricula, emphasizing the need for a nuanced approach to religious education within the broader educational framework. Recognizing and addressing these consequences can contribute to building a more tolerant and cohesive society